Cell Viability of Normal Human Skin Fibroblast and Fibroblasts Derived from Granulation Tissue: Effects of Nutraceuticals - Borawska, M. H.; Czechowska, S. K.; Markiewicz, R.; Hayirli, A.; Olszewska, E.; Şahin, Kazım (Mary Ann Liebert, Inc, 2009)
The effects of lycopene, genistein, and epigallocatechin-3-gallate (EGCG) on cell viability were tested in vitro using a normal human skin fibroblast (NHSF) cell line (CRL-1474) and granulation tissue fibroblasts (GTFs) obtained from a patient with middle ear cholesteatoma. Cell cultures were added with lycopene (1, 5, and 10 mu M), genistein (1, 5, 10, 25, and 50 mu M), and EGCG (1, 5, 10, 25, and 50 mu M) and their respective control cultures were established by adding 5 mL/L tetrahydrofuran (THF), 5 mL/L dimethyl sulfoxide (DMSO), and 5 mL/L DMSO. A colorimetric assay was employed for determining cell viability using thiazolyl blue tetrazolium bromide. Cell viability was expressed as a percentage of the control. Data were analyzed using two-way analysis of variance separately for each compound. Lycopene addition decreased viability of NHSFs and GTFs compared with THF addition (64.1%, 60.5%, and 100%, respectively, P < .0001). Genistein addition also increased viability of both NHSFs and GTFs compared with DMSO addition (P < .02). Increasing EGCG concentration tended to cause a linear increase in viability of NHSFs but did not alter viability of GTFs (P < .10). Our data suggest that genistein and EGCG but not lycopene could help maintaining or improving skin health through enhancing viability of skin fibroblasts.
Keywords: epigallocatechin-3-gallate; fibroblast viability; functional food; genistein; lycopene; skin health